Chitosans of different molecular weight enhance potato (Solanum tuberosum L.) yield in a field trial - Falcón-Rodríguez, Alejandro B.; Costales, Daimy; Gónzalez-Peña, Dianevys; Morales, Donaldo; Mederos, Yuliem; Jerez, Eduardo; Cabrera, Juan C. (Spanish Journal of Agricultural Research, 2017)
Physico-chemical features of chitosan affect its biological activity on plants. In this work, the influence of chitosan molecular mass in potato (Solanum tuberosum L.) yields was investigated. By using chitosan polymers of high (CH-1) and low (CH-2) molecular weight and a hydrolysed chitosan derivative (CHH), two experiments were performed under field conditions to determine the effect of these polymers on yields of two potato varieties, ‘Call White’ and ‘Santana’. For this purpose, the foliar spray of low doses of the derivatives at three cultivation moments was performed and several yield variables were determined at crop harvest. All three chitosan compounds increased the performance variables determined respect to the control, depending on the variable, the dose employed and the mass of the derivative evaluated. In most variables determined, the two lowest doses (200 and 325 mg/ha) provoked the highest increments above control. Chitosans also affected distribution of mass per tuber size, particularly; in ‘Santana’ variety the two lowest doses enhanced the commercial tuber sizes. Among the polymers, CH-1 caused the greatest increases in performance, while, compared to the polymer, CHH provoked higher yields. In conclusion, foliar application at low doses of high molecular weight and hydrolysed chitosan enhanced potato yield between 15-30%.